Transfer of watershed technology for sustained yield forestry in Malaysia. - Nik Ab. Majid, Nik Muhamad; Jusoff, Kamaruzaman (1986)
The transfer of watershed technology is a vital factor for sustained yield forestry in Malaysia. In this paper the importance of watershed for sustained yield forestry in Malaysia is discussed. The processes involved in the development and transfer of watershed technology were identified. Several constraints were posed and needs and priorities were pointed in the transfer of technology in watersheds. The establishment of a Watershed Management Technology Transfer Center (WMTTC) in Malaysia was strongly proposed. It is contended that a multi-disciplinary approach to the analysis of the problem of watershed technology transfer at all levels is required if new technology is to make perceptible impact on watershed management in Malaysia.